Effect of triphala kwathprakshalanin the management of carbuncle (prameha pidika)”: A case study - Pankaj Thakur; Vishalverma; Sheetalverma; Mahesha Chandra; Neelam Sahu; Vandana Chauhan (International Journal of Pharmacy and Analytical Research, 2022)
Carbuncle is an uncommon skin and soft tissue infection, predominantly occurring in diabetics. It is quite surprising that there are very few series on carbuncle over last 2-3 decades. It is painful, pus-filled bumps forming due to bacterial infection resulting in inflammation of one or more hair follicles. Carbuncles are likely to occur on hairy areas of the body particularly at the back of the neck. But they may also be found on shoulders, thighs, groin, buttocks, and armpits. Carbuncles are very infectious too and may spread to other parts of the body and even to other people.The initial cause of a carbuncle can often not be determined. Poor health may be a predisposing factor like Chronic skin conditions, diabetes, kidney disease, liver disease and weak immune system, folliculitis, friction from clothing or shaving, having hair pulled out, generally poor hygiene, poor nutrition. Diagnosis of Carbuncles by merely looking at the affected area, Pus sample, blood test span of the Carbuncle if lasts for two weeks, lesion culture, Urine test. If it is untreated, it may causes serious complications like sepsis and infections in other parts of the body. In modern, treatment are Antibiotics and incision at the tip of the carbuncle and drain out the pus but not get much relief. In Ayurveda describes carbuncle as pidaka, one of the major complications of diabetes mellitus. Acharya susrutha explains carbuncles as 10 types. A 60 year old diabetic male patient was presented of small nodule in his right buttock with pain and pus discharge. Triphala kwath prakshalan done for 15 days and heal satisfactory. Triphala have antimicrobial and anti-inflammatory property and balance the tri-doshas. Triphala proved to be an efficient measure in carbuncle.